Understanding Venenata Dermatitis and its Toxin: Case Report - Godianto, Felicia; Suhardi, Silvi (Jurnal Ners, 2024)
Dermatitis venenata refers to a skin irritation reaction resulting from bites or direct contact between the skin and the saliva or hair of insects. This contact manifests as distinctive red patches on the skin, which may extend to surrounding areas and develop into painful blistering lesions. These lesions often exhibit a spreading pattern in areas of contact, commonly known as "kissing lesions." Without proper management, these blisters may lead to skin infections or leave lasting scars. Venenata dermatitis, linked to the Paederus genus toxin paederin, often occurs in warm, tropical regions. It presents with blistering, red skin, vesicular papules, and pustules in diverse patterns 8 to 24 hours after toxin exposure. Predominantly affected areas include the face, neck, shoulders, arms, and waist. "Kissing lesions" emerge when the initial lesion transfers to adjacent normal skin. Prompt diagnosis of dermatitis venenata is crucial, serving as a proactive measure to prevent exacerbation. Swift identification plays a pivotal role in facilitating timely interventions and implementing preventive strategies, reducing the risk of worsening symptoms. This expeditious diagnostic process is central to safeguarding against symptom escalation and ensuring effective management for overall skin health. In our case, a 27-year-old woman presented symptoms of redness, stinging, and itching around her neck area. Initially manifesting as redness, the condition progressed to blister-like formations within a few hours. The diagnosis of venenata dermatitis was established based on the patient’s reported symptoms and objective findings from the dermatological examination. The physical examination revealed a well-defined red plaque with vesicles and erosions localized on the right side of the neck.